PERAN TANAMAN HERBAL SEBAGAI TERAPI TAMBAHAN DALAM PENANGANAN ASMA: TINJAUAN SISTEMATIS LITERATUR - Nazwa Aliefia Adzani; Riki Nova (Yayasan Nusantara Hasana Berdikari, 2025)
Asthma is a chronic inflammatory respiratory disease that poses major challenges in its diagnosis and management. Modern asthma therapy has limitations, especially the side effects of synthetic drugs. Therefore, the use of herbal plants as an additional therapy is a potential alternative. This article is a literature review using the systematic review method with the PRISMA diagram. The literature was searched through the Google Scholar and PubMed databases using the keywords